Manual on Fiscal Transparency, revised April 2007. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The Manual, which is a companion document to the IMF's Code of Good Practices on Fiscal Transparency (2007), has been revised to reflect the new Code and to provide more recent examples of good practice by individual countries. The Manual expands and explains the pillars and principles of the Code and provides richer and more in-depth coverage of each good practice. Country examples are taken from Reports on Standards and Codes (ROSCs). The Manual also includes new linkages to the Guide on Resource Revenue Transparency (2007), including reporting on contracts, quasi-fiscal activities and use of public assets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet